Application of Polarization and Depolarization Current in High Voltage Insulator - A Review - Sunthrasakaran, Nishanthi; Mohd Jamail, Nor Akmal; Mohd Jamail, Nor Shahida; Baharom, Md Nor Ramdon; Mohamed Piah, Mohamed Afendi; Kamarudin, Qamarul Ezani; Sies, Mohamad Farid; Othman, Nordiana Azlin; Abd Rahman, Rahisham (International Journal of Integrated Engineering, 2020)
Deterioration of cable insulator can be caused by many factors such as aging, fault and breakdown. These factors are caused by the presence of moisture, impurities and heat due to high temperatures in an insulator. The maintenance and replacement for insulation system in power cables, power transformers and electric machine stator are generally expensive and time consuming. Thus, the performance and ability of an insulator can be monitored through polarization and depolarization current (PDC). Polarization and depolarization current (PDC) is a non-destructive test method that is used to analyse many factors that affects the behaviour of an insulator in time domain. This paper presents the review on application of polarization and depolarization current test method on different type of insulator. The factors that affects the performance of different type of insulator will be discussed in this paper. Moreover, the theory of polarization and depolarization current will be explained in order to understand the behaviour of polarization and depolarization current curve when fault occurs. Last but not least, this paper will provide a review on the different type of factors that affects the performance of different types of insulation.